2019
DOI: 10.33899/ijvs.2019.162994
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of mycotoxins in broiler’s local and imported feeds

Abstract: In the present study 40 samples of broiler feeds that obtained from commercial feed manufacturing company (concerning 21 from Iraqi manufactures and 19 from the Iranian manufactures) were analyzed for the incidence of Aflatoxins, Ochratoxin, T-2, Fumonisins, and Zearalenone mycotoxins. The result has shown that AF was detected in 16 samples 76.19% of the Iraqi manufactures and 16 samples 84.21% from the Iranian manufactures, in concentrations ranging from 1.00-23.00 μg/ kg, and 1.00-2.00 μg/ kg respectively. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The results of this study show that several drinking water samples have exceeded the allowable limit for the validity of drinking water according to the Iraqi Criteria and Standards of water's microbial limits 11 , which is zero cfu /100ml. This study coincided with previous studies of 5 which reported that the presence of bacteria in drinking water may be due to the lack of chlorine effects due to low levels of chlorine pumped into the network also to the breaks and cracks in the net pipes which may lead to a mix of drinking water with polluted water resulted from the cracks in the sewage net pipes or groundwater 15,16 .…”
Section: Fs Cfu /100mlsupporting
confidence: 91%
“…The results of this study show that several drinking water samples have exceeded the allowable limit for the validity of drinking water according to the Iraqi Criteria and Standards of water's microbial limits 11 , which is zero cfu /100ml. This study coincided with previous studies of 5 which reported that the presence of bacteria in drinking water may be due to the lack of chlorine effects due to low levels of chlorine pumped into the network also to the breaks and cracks in the net pipes which may lead to a mix of drinking water with polluted water resulted from the cracks in the sewage net pipes or groundwater 15,16 .…”
Section: Fs Cfu /100mlsupporting
confidence: 91%
“…Other factors that boosted disinfection resistance were biofilm age, bacterial encapsulation, and prior growth circumstances, which raised chlorine resistance by 2-to 10-fold. Because water treatment facilities cannot eradicate all Coliforms, the effectiveness of drinking water treatment against gram-negative bacterial isolates should be checked regularly 25 . Chlorine-resistant microbiological species should be retrieved from chlorinated water distribution systems if they exist 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, DPW positively impacts increasing metabolism and transferring most carbohydrates from leaves to fruits. In addition, organic matter can provide plants with the necessary nutritional elements such as nitrogen and phosphorous, which enhance carbon metabolism, respiration, and protoplasts, form nucleic acids, DNA, and RNA, and accelerate cell division 20 . Thus, the presence of these nutrients in the organic matter can increase the protoplasm mass and accelerate cellular div 21 .…”
Section: Quantitative and Qualitative Indicatorsmentioning
confidence: 99%